Regulation of affect by the lateral septum: implications for neuropsychiatry - Sheehan, Teige P; Chambers, R.Andrew; Russell, David S (Brain Research Reviews, 2004)
Substantial evidence indicates that the lateral septum (LS) plays a critical role in regulating processes related to mood and motivation. This review presents findings from the basic neuroscience literature and from some clinically oriented research, drawing from behavioral, neuroanatomical, electrophysiological, and molecular studies in support of such a role, and articulates models and hypotheses intended to advance our understanding of these functions. Neuroanatomically, the LS is connected with numerous regions known to regulate affect, such as the hippocampus, amygdala, and hypothalamus. Through its connections with the mesocorticolimbic dopamine system, the LS regulates motivation, both by stimulating the activity of midbrain dopamine neurons and regulating the consequences of this activity on the ventral striatum. Evidence that LS function could impact processes related to schizophrenia and other psychotic spectrum disorders, such as alterations in LS function following administration of antipsychotics and psychotomimetics in animals, will also be presented. The LS can also diminish or enable fear responding when its neural activity is stimulated or inhibited, respectively, perhaps through its projections to the hypothalamus. It also regulates behavioral manifestations of depression, with antidepressants stimulating the activity of LS neurons, and depression-like phenotypes corresponding to blunted activity of LS neurons; serotonin likely plays a key role in modulating these functions by influencing the responsiveness of the LS to hippocampal input. In conclusion, a better understanding of the LS may provide important and useful information in the pursuit of better treatments for a wide range of psychiatric conditions typified by disregulation of affective functions.